Proximate, Mineral and Antinutrient Contents of Cocoyam (Xanthosoma sagittifolium (L.) Schott) from Ethiopia - Eyasu Wada; Tileye Feyissa; Kassahun Tesfaye (International Journal of Food Science)
Cocoyam (Xanthosoma sagittifolium (L.) Schott) is an important food crop especially in the tropics and subtropics. Its cormels and leaves are eaten after cooking in the rural areas in Ethiopia. There is lack of information on the nutritional composition of cocoyam grown in the country. In this study, cormels of green- and purple- cocoyams were analyzed to determine proximate and mineral contents and antinutritional factors. The moisture contents (%) of green- and purple-cocoyams were 61.91 and 63.53, respectively. Crude protein (10.10%) and fiber (2.66%) contents of purple cocoyam were significantly higher than crude protein (8.48%) and fiber (2.14%) contents of green cocoyam. Fat contents (%) of the green- and purple cocoyam were 0.85 and 0.22, respectively. Ash content of green cocoyam (3.25%) was significantly higher than the ash content of purple cocoyam (2.27%). The carbohydrate contents (%) and gross energy values (kcal/100 g) of green- and purple-cocoyam, respectively, were 85.36 and 378.47 and 84.76 and 380.27, showing that cocoyam grown in Ethiopia can be a good source of energy. Mineral contents (mg/100 g) of green cocoyam were determined as Fe (8.20), Zn (3.07), Cu (1.04), Mg (78.77), Mn (2.48), P (120.93), Na (29.22), K (1085.70) and Ca (56.57) while purple cocoyam had Fe (9.88), Zn (3.12), Cu (1.14), Mg (82.00), Mn (3.74), P (129.87), Na (24.33), K (1223.30) and Ca (44.90). High antinutritional factors (phytate and tannin) (mg/100 g) were determined from both green- and purple-cocoyam genotypes with significantly higher quantities in purple cocoyam (187.57 phytate and 156.1 tannin) than the green cocoyam (167.76 phytate and 139.62 tannin). This study provided important information about the nutritional composition of cocoyam from Ethiopia, which can help to develop cocoyam food products and to promote production and utilization of cocoyam by encouraging its sustainable use. More detailed analyses including processing and sensory testing are suggested for further investigation in order to obtain healthful and comfortable cocoyam products.